Variation of the rainfall regime in the Northern region and its effect on the Odonata (Insecta) in Been river, Amazonas, Brazil - Fulan, Joao Anderson; Anjos, Marcelo Rodrigues dos (Instituto de Ecología, A.C., 2019)
The goal of this work was to know the effect of precipitation in four periods (Rising, Flood, Lowing and Dry) on Odonata larvae living near to the macrophyte Salvinia auriculata Aubl., in Been River, Amazonas, Brazil. The biological material was collected in the Been river in the section near the river Madeira, state of Amazonas, Brazil. Sampling was conducted in stands of three macrophytes S. auriculata in four periods: rising (November 2012), flood (February 2013), lowing (May 2013), and dry (August 2013). A total of 286 Odonata larvae were identified in the river studied. Six families and 14 genera were identified. The flood period showed the highest abundance in the studied period. Acanthagrion presented a positive correlation with flood period in axis 1 and Telebasis also positive, but in the dry period. In conclusion, although there are few studies on Odonata larvae associated with floating macrophytes in the Amazon, the results of this work showed the importance of knowing the distribution of larval abundance throughout the year. Flood and dry period showed to be the period with the highest abundance of Odonata genera. In addition, the principal component analysis showed that some species are more sensitive to the periods of the year, Telebasis in the dry period and Acanthagrion in the flood period.